Economic Price Searching, Quality Seeking, Value Deriving Behavior of Women and Their Relationship with Demographics and Loyalty : An Empirical Study - Roy, Saswati; Mandal, Kaushik (Indian Journal of Marketing, 2021)
The relationship between shopping orientation and each of the demographic variables namely age, income, and education is well established for the general consumer. Similarly, brand loyalty is also well associated with different facets of shopping for them. Since there is not enough evidence of work to justify the above relationship specifically for women when literature has acknowledged that women are behaviorally different from men, we can consider this non-availability of empirical proof of the stated relationship in the case of women as one of the research gaps. As all the research pieces of evidence for the above-mentioned relationship were from developing nations, it unfolds another research gap. To mitigate both the gaps, we carried out a principal component analysis to identify shopping oriented facets for Indian women consumers and in the second stage tried to relate the same in isolation with the mentioned demographic variables (namely age, income, and education) and brand loyalty. The results revealed that Economic Price Searching Behavior (EPSB) was one of the shopping orientation facets significantly associated with age, income, and brand loyalty ; Quality Seeking Behavior (QSB) was another facet that was significantly associated with income and brand loyalty ; and Value Deriving Behavior (VDB), as the last facet, was significantly associated with income and brand loyalty.